?EXTRACTION OF ALUMINA FROM NEPHELLINE SYENITE BY SINTERING WITH LIMESTONE - KHAN, MUMTAZ; RIAZ, M.; KHAN, KAMIN (Biological Sciences - PJSIR, 1996)
Nepheline Syenite of Koga (Lower Swat area) Pakistan was sintered at 125°C with suitable quantity of lime- stone followed by water leaching for the formation of alkali abuminates which are further processed for the extrac- tion of alumina. Parameters such as particle size variation, ratio of nepheline syenite and limestone, time tempera- ture of sintering and sodium hydroxide concentration were optimized to obtain maximum recovery of alumina. The extraction of alumina on the basis of alumina in Nepheline synite has been found to be about 70%. Such a process may be of vital importance to countries without ready access to supplies of alumina in the form of bauxite.